Association of Combined Healthy Lifestyle Factors With Incident Dementia in Patients With Type 2 Diabetes. (22nd November 2022) - Wang, Bin; Wang, Ningjian; Sun, Ying; Tan, Xiao; Zhang, Jihui; Lu, Yingli
Abstract : Background and Objectives: Type 2 diabetes and lifestyle factors have been associated with dementia risk, but the effect of a healthy lifestyle on diabetes-related dementia remains largely unknown. We aimed to investigate whether the increased risk of dementia among individuals with diabetes can be offset by a broad combination of healthy lifestyle factors. Methods: This prospective study used data from the UK Biobank cohort. An overall lifestyle score ranging from 0 to 7 was created, with 1 point for each of the 7 healthy lifestyle factors: no current smoking, moderate alcohol consumption, regular physical activity, healthy diet, adequate sleep duration, less sedentary behavior, and frequent social contact. Incident dementia was ascertained using linkage with electronic health records. Cox proportional hazards models were used to examine the associations between diabetes, healthy lifestyle score, and dementia incidence. Results: We included 167, 946 participants aged 60 years or older without dementia at baseline (mean age 64.1 [SD 2.8] years, 51.7% female). During a median follow-up of 12.3 years, 4, 351 developed all-cause dementia. Participants with diabetes, but not those with prediabetes, showed a higher risk of dementia than those with normoglycemia. Compared with diabetes-free participants who had a lifestyle score of 7, the hazard ratios (HRs) for dementia were 4.01 (95% CI 3.06–5.25) and 1.74 (95% CI 1.11–2.72) for those with diabetes who had a lifestyle score of 0–2 and 7, respectively. Among participants with diabetes, the HR for dementia comparing a lifestyle score of 7 vs 0–2 was 0.46 (95% CI 0.28–0.75). This finding corresponded to a reduction in the 10-year absolute risk of dementia from 5.22% (95% CI 3.94%–6.73%) to 1.72% (95% CI 0.92%–2.97%). The association between higher lifestyle score and lower dementia risk was independent of glycemic control and diabetes medication. Discussion: Adherence to a broad range of healthy lifestyle factors was associated with a significantly lower risk of dementia among participants with diabetes. Behavioral lifestyle modification through multifactorial approaches should be a priority for prevention and delayed onset of dementia in patients with diabetes.